The cyclic di-GMP receptor YcgR links the second messenger with the putrescine quorum sensing system in modulation of Dickeya oryzae motility - Weihan Gu; Yufan Chen; Congcong Xie; Zhongqiao Chen; Huagui Gao; Yaping Zhu; Lian-hui Zhang; Lisheng Liao (mBio)
ABSTRACT Dickeya oryzae is a prevalent pathogen capable of infecting a variety of crops and plants, and its cell motility plays a key role in invasion of host and subsequent systemic infection. We recently demonstrated that the bacterial second messenger c-di-GMP and the putrescine (PUT)-mediated quorum sensing (QS) system are, respectively, involved in negative and positive regulation of bacterial motility, and vice versa, biofilm formation. In this study, we aimed to investigate the potential interaction of these two signaling mechanisms in the modulation of bacterial motility. The results indicated that null mutation of the PUT system did not seem to have much effect on the cellular level of c-di-GMP; however, deletion of the genes encoding c-di-GMP degradation led to a significant reduction in PUT production. A subsequent study unveiled that the second messenger signaling system interacted with the putrescine QS system through the c-di-GMP receptor YcgR. This interaction enhanced the activity of SpeA, which is the rate-limiting enzyme in the putrescine biosynthesis pathway, resulting in increased intracellular putrescine level. Critically, this facilitative effect was inhibited by c-di-GMP molecules; thus, SpeA, YcgR, and c-di-GMP constitute a regulatory loop modulating D. oryzae motility by controlling the rate of putrescine biosynthesis. The findings from this study provide the first insight into the interaction mechanism between c-di-GMP and putrescine signaling systems in bacteria.IMPORTANCEDickeya oryzae is an important bacterial pathogen that can infect numerous plants and crops, leading to substantial economic losses, especially in rice and banana cultivation. Bacterial motility is a crucial pathogenic factor for D. oryzae as it enables the pathogen to compete for food resources and invade host plants. This motility is negatively regulated by the second messenger c-di-GMP and positively regulated by the quorum sensing signal putrescine (PUT). However, the potential connection between c-di-GMP and PUT signaling systems in regulating the motility of D. oryzae has not been understood. Here, we reveal the link and mechanism of the interaction between them, demonstrating that c-di-GMP interacts with the PUT system via its receptor YcgR. The significance of our research lies in providing the first insight into the molecular interaction between c-di-GMP and PUT signaling networks, both of which are widely conserved signaling mechanisms, and sheds light on the complex and sophisticated regulatory mechanisms that govern bacterial motility and virulence.